Komunikasi Orang Tua dan Anak Ketika Mendampingi Anak Belajar di Masa Pandemic Covid-19 - Mohammad Chairul Fajri; Oji Kurniadi (UNISBA Press, 2022)
Abstract. This article aims to find out how the role of parents or parent-child communication during learning at home because it is during the covid-19 pandemic, therefore researchers want to know how to teach or how to communicate from mothers who still have children who are still sitting on the bench. primary school. By wanting to know how to communicate parents to children in terms of learning at home, whether using verbal or non-verbal communication. In addition to communicating how parents guide their children to learn, how can parents be a motivator for their children. Therefore, researchers want to know how parents in children's learning become motivators, motivators, and others. The technique in this research is to use descriptive qualitative methods with data collection techniques using interviews so that the information can be accurate and appropriate, and to find out besides making a living how to teach parents to children during home learning or online learning. The results of this study are that both verbal and non-verbal communication are communication which are both useful in guiding children to learn, because by communicating between parents and children, parents can help children in guiding children to learn, so that the child can do the learning. properly and correctly. Suggestions for the future, that parents should often communicate with children especially regarding guiding children's learning, because if parents do not communicate often, then parents will not understand what the child is doing, and children's learning will be difficult or slow, due to lack of communicate between parents and children, because guidance and support from parents can make children more enthusiastic about learning. Abstrak. bertujuan untuk mengetahui bagaimana peran orang tua atau komunikasi orang tua kepada anaknya selama pembelajaran dirumah karena lagi dalam masa pandemic covid-19, maka dari itu peneliti ingin mengetahui bagaimana cara mengajar atau cara berkomunikasi dari ibu yang masih memiliki anak yang masih duduk di bangku sekolah dasar. Dengan ingin mengetahui bagaimana cara berkomunikasi orang tua kepada anak dalam hal pembelajaran dirumah,apakah menggunakan komunikasi verbal atau non verbal. Selain cara berkomunikasi bagaimana cara orang tua dalam membimbing anak belajar,bagaimana orang tua bisa menjadi motivator bagi anaknya tersebut. Maka dari itu peneliti ingin mengetahui bagaimana cara orang tua dalam pembelajaran anak menjadi motivator, pendorong,dan lain-lain. Tehnik dalam penelitian ini yaitu mengunakan metode kualitatif deskriptif dengan tehnik pengumpulan data menggunakan cara dengan wawancara agar informasi tersebut bisa akurat dan pas,serta agar mengetahui selain mencari nafkah bagaimana cara mengajar orang tua kepada anak selama pembelajaran di rumah atau pembelajaran daring. Hasil dari penelitian ini yaitu dari kedua komunikasi verbal dan non verbal merupakan komunikasi yang memang keduanya berguna dalam membimbing anak belajar, karena dengan berkomunikasi antara orang tua dan anak, maka orang tua bisa membantu anak dalam membimbing anak belajar,